Pengaruh Interaksi Orang Tua-Anak terhadap Pembentukan Pola Pikir dan Sikap Anak - Chintami Azzahra; Cut Alya Putri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study, titled “The Influence of Parent-Child Interaction on the Development of Children’s Mindset and Attitudes,” is conducted through a literature review of various theories and previous relevant studies. The aim of this research is to identify the role of parent-child interactions in shaping children’s mindset and attitudes from early childhood to adolescence. Based on the literature analysis, it is found that high-quality interactions—such as open communication, positive role modeling, and consistent emotional support—significantly contribute to the development of critical thinking, empathy, and self-confidence in children. Conversely, authoritarian parenting styles, lack of communication, or unresponsiveness to children’s emotional needs tend to foster closed-mindedness, aggressive behavior, and poor social adaptability. This study highlights the essential role of parents in creating a supportive family environment for optimal character development in children.